Análise da eficácia luminosa de sistemas de iluminação com comunicação agregada - Teixeira, Lucas (2020)
Visible light communication (VLC) currently receives attention in the consumer electronics media mainly because of the potential to improve the data rate of Internet access in short range mobile communications, yet several other new applications can be made feasible using this emerging technology. VLC uses modulation of light unperceptive to the human sight, most frequently implemented with light emitting diodes (LED), for transmitting information and simultaneously useful illumination is provided. However, despite the intense research activity on this subject, on the technical side there are open questions and a clear disconnection among the published solutions and the actual ground for reusing the visible light for communication. The energy consumption is a key aspect that is a concern considering the illumination purpose and also is reflected in the communication features, since aggregating such functionality to any light fixture may require design changes and affects LED’s operational conditions. Therefore, in this thesis a comprehensive study is presented approaching the concerns on the design of a VLC transmitter, which accounts for illumination and communication aspects, focusing mainly on the extra energy consumption caused by aggregating the communication purpose. The systematization of the published literature allowed for understanding the trends in the development of this technology. Also, the overview of a transmitter device allowed for pointing out the best design choices in selecting modulation schemes and LED driver circuits for VLC. The discussion about the signal power and bandwidth is also considered throughout the development of the analysis aiming at reducing the energy consumption and increasing transmission data rates. This work presents results that indicate switching mode modulators as adequate for narrower bandwidth applications, although these recently received significant research attention for improving modulation bandwidth capability. The link power budget analysis leads to the conclusion that linear power amplifiers used as modulators for VLC require much lower extra energy for implementing wider bandwidth signaling, even though they work based on a dissipative principle.